PENGEMBANGAN USAHA KELOMPOK PRODUSEN DADIH DI KECAMATAN TILATANG KAMANG - Amna Suresti; Salam N Aritonang; Rahmi Wati (Jurnal Hilirisasi IPTEKS, 2018)
This article describes the results of the community service activities for training, coaching and mentoring on producer dadih groups in the District Tilatang Kamang . This activity aims to: 1) increase the motivation of entrepreneurial partners; 2) increase the insight and knowledge of maintenance management buffaloes; 3) improve the ability of the partners to diversify into multiple product dadih and 4) developing the marketing area. The results of this activity are: 1) increase the entrepreneurial spirit partner as efforts to support the development of the group; 2) Activity buffaloes maintenance management counselling can improve insight and knowledge in raising livestock breeder buffalo; 3) Training and the pilot was able to increase revenue diversification dadih and 4) The promotion and development of network marketing has been used as a marketing strategy to increase the production volume of business groups.